2014
DOI: 10.1111/tra.12148
|View full text |Cite
|
Sign up to set email alerts
|

CNIH4 Interacts with Newly Synthesized GPCR and Controls Their Export from the Endoplasmic Reticulum

Abstract: The molecular mechanisms regulating G protein-coupled receptors (GPCRs) trafficking from their site of synthesis in the endoplasmic reticulum (ER) to their site of function (the cell surface) remain poorly characterized. Using a bioluminescence resonance energy transfer-based proteomic screen, we identified a novel GPCR-interacting protein; the human cornichon homologue 4 (CNIH4). This previously uncharacterized protein is localized in the early secretory pathway where it interacts with members of the 3 family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 61 publications
0
48
1
1
Order By: Relevance
“…Among four CNI homologs (CNIHs) in mammals, CNIH2 and CNIH3 function as α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) receptors for glutamatergic neurotransmission in the central nervous system (Herring et al, 2013;Jackson and Nicoll, 2009;Schwenk et al, 2009). CNIH4 interacts with both G-protein-coupled receptors (GPCRs) and Sec23 and Sec24 and, thus, acts as a cargo receptor for recruiting GPCRs into COPII vesicles and transporting them to the cell surface (Sauvageau et al, 2014). Additionally, human CNIs functionally complement the loss of Erv14 in yeast (Castro et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Among four CNI homologs (CNIHs) in mammals, CNIH2 and CNIH3 function as α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) receptors for glutamatergic neurotransmission in the central nervous system (Herring et al, 2013;Jackson and Nicoll, 2009;Schwenk et al, 2009). CNIH4 interacts with both G-protein-coupled receptors (GPCRs) and Sec23 and Sec24 and, thus, acts as a cargo receptor for recruiting GPCRs into COPII vesicles and transporting them to the cell surface (Sauvageau et al, 2014). Additionally, human CNIs functionally complement the loss of Erv14 in yeast (Castro et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TARPs are essential for ER export of correctly assembled receptors 85 and remain part of the AMPAR complex throughout Golgi processing and forward trafficking to eventual surface expression at the postsynaptic density 86 . Similarly, cornichons have a welldefined role in the export of specific proteins from the ER 87,88 including AMPARs 89,90 .…”
Section: Rna Editing Ampar Assembly and Er Exitmentioning
confidence: 99%
“…To date, several integral membrane cargo, including TGFα, AMPA receptors, and G protein-coupled receptors (GPCRs), are known to depend on Cornichon function for efficient delivery (Bokel et al 2006, Sauvageau et al 2014, Schwenk et al 2009). Systematic studies in yeast have identified more than 30 transmembrane cargo proteins that accumulate in the ER when cells are deleted for Erv14 (Herzig et al 2012, Pagant et al 2015.…”
Section: Cornichon Proteinsmentioning
confidence: 99%
“…Regulation can be coupled to signaling pathways. In addition to the role of SCAP and iRhom2 discussed, a well-studied example of regulation is provided by GPCRs, for which many membrane-associated and cytosolic effector molecules that regulate ER-to-Golgi traffic have been identified (Achour et al 2008, Dong et al 2007, Sauvageau et al 2014. One such effector is Rab acceptor family 2 (PARF2), a protein that serves as a gatekeeper in the ER for the GB1 subunit of the GABA B receptor (Doly et al 2015).…”
Section: Fine-tuning Of Protein Deploymentmentioning
confidence: 99%